Comparing the Effect of Stretching and Muscle Energy Technique in the Management of Lower Cross Syndrome - Nouman Khan, Munazza Nouman, Muhammad Affan Iqbal, Kinza Anwar, Abdul Ghafoor Sajjad, Syed Ali Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the effects of stretching exercises & muscle energy techniques in the management of lower cross syndrome. Methods: In this parallel, randomized controlled trail fifty-eight patients were randomly assigned into two intervention groups. Group A received stretching technique and Group B received muscle energy technique, three sessions per week for total duration of four weeks. Results: Normality test applied and P values were noted by applying Shapiro-Wilk test both groups. Baseline measures for both groups showed no significant difference as the P value > 0.05. The paired t-test within the group of Stretching and Muscle Energy Technique showed significant difference in pre and post Numeric Pain Rating Scale (NPRS), pre and post Oswestry Disability Index (ODI) and pre and post muscle length via inclinometer and goniometer. Independent t-test for post treatment groups between stretching group and muscle energy technique group was not significant i.e. P> 0.05. Conclusion: The study concluded that statistically there is no significant difference in variables of both groups i.e. Numeric Pain Rating Scale (NPRS), Oswestry Disability Index (ODI), bilateral muscle length of iliopsoas, hamstrings and rectus femoris as well as of erector spinae. However, mean values of above mentioned parameters show a little more improvement in Muscle Energy Technique group.